1989
DOI: 10.1123/pes.1.3.195
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Motivation for Participation in and Withdrawal from Sport: Identifying the Missing Links

Abstract: Children’s reasons for participating in sport as well as their reasons for discontinuing involvement have been extensively studied over the last decade. However, a complete understanding of the underlying processes influencing these phenomena has been clouded by failing to consider a number of individual difference and contextual factors related to sport participation. These missing links include participant status group differences, program type, level of intensity, type of sport, particular reasons for attri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
68
0
12

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(83 citation statements)
references
References 0 publications
3
68
0
12
Order By: Relevance
“…Research focused on motivation for sports participation has also identified perceived competence, enjoyment, social connectedness, and degree of outside pressure as primary motives for pursuing or dropping out of sports (Brustad, Babkes, & Smith, 2001;Fredricks, et al, 2002;Patrick, et al, 1999;Weiss & Petlichkoff, 1989;Weiss & Williams, 2004). Characteristics of OST settings that are thought to increase participation and support the need for relatedness, autonomy, and competence include:…”
Section: Mechanisms For Promoting Youth Pa In Camp Settingsmentioning
confidence: 99%
“…Research focused on motivation for sports participation has also identified perceived competence, enjoyment, social connectedness, and degree of outside pressure as primary motives for pursuing or dropping out of sports (Brustad, Babkes, & Smith, 2001;Fredricks, et al, 2002;Patrick, et al, 1999;Weiss & Petlichkoff, 1989;Weiss & Williams, 2004). Characteristics of OST settings that are thought to increase participation and support the need for relatedness, autonomy, and competence include:…”
Section: Mechanisms For Promoting Youth Pa In Camp Settingsmentioning
confidence: 99%
“…The main reasons for young people to participate in sports are related to the quality of their engagement, that is, with their enjoyment of and interest in the sport (Castillo, Balaguer, & Duda, 2000;Gill, Gross, & Huddleston, 1983), whereas lack of enjoyment is an important determinant of sport drop-out (Gill et al, 1983;Weiss & Petlichkoff, 1989). Moreover, the desire for enjoyment has been positively related to a higher frequency of sports participation (Frederick, 1999).…”
mentioning
confidence: 99%
“…In line with these results, our research data has shown that most of the parents surveyed, when asked their opinion about physical and sporting habits, agreed that participating in these activities is good for your health. This reason coincides completely with those mentioned in previous studies aimed at elucidating why parents enrol their children in extracurricular sporting programmes: they want them to enjoy themselves, have fun and do exercise (Passer, 1982;Weiss & Petlichkoff, 1989;Gill, 1992;McCullagh et al, 1993;Cruz, 1997).…”
Section: Volume 8 | Issue 3 | 2013 | 871mentioning
confidence: 48%